2018
DOI: 10.1016/j.sse.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Design optimization and fabrication of a novel structural piezoresistive pressure sensor for micro-pressure measurement

Abstract: This paper presents a novel structural piezoresistive pressure sensor with a four-beams-bossed-membrane (FBBM) structure that consisted of four short beams and a central mass to measure micro-pressure The proposed structure can alleviate the contradiction between sensitivity and linearity to realize the micro measurement with high accuracy In this study, the design, fabrication and test of the sensor are involved By utilizing the finite element analysis (FEA) to analyze the stress distribution of sensitive ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…c Comparison of the von Mises stresses of the three structure types. d Four-beam-bossed-membrane (FBBM) structure (front and back review) 50 . e Back review of FBBM 50 .…”
Section: Minute Differential Pressure Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…c Comparison of the von Mises stresses of the three structure types. d Four-beam-bossed-membrane (FBBM) structure (front and back review) 50 . e Back review of FBBM 50 .…”
Section: Minute Differential Pressure Sensorsmentioning
confidence: 99%
“…d Four-beam-bossed-membrane (FBBM) structure (front and back review) 50 . e Back review of FBBM 50 . f Stress distribution curve of the path 50 .…”
Section: Minute Differential Pressure Sensorsmentioning
confidence: 99%
“…Sensors with different mechanisms have their own advantages and limitations in pressure sensing range, sensitivity, response time, working frequency, array integration and other aspects, which make them suitable for different applications (Ji et al , 2016). For example, a piezoresistive sensor with a four-beams-bossed-membrane (FBBM) structure that consisted of four short beams and a central mass to measure micropressure is sensitive to 4.65 mV/V/kPa in the operating range of 0–5 kPa at room temperature and can measure absolute micropressures up to 5 kPa, however, it suffers from hysteresis and therefore has poor frequency response characteristics (Li et al , 2018). A capacitive sensor, whose structure is based on a wafer bonding technology to integrate and package capacitive force sensor using silicon diaphragm and an integrated circuit separately manufactured, has good frequency response, with linear sensitivity of 57,640 Hz/N and fluctuation of 10 mN, while it is susceptible to noise, so complex electronic devices are needed for filtering (Mitsutoshi et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 5 ] introduced a novel plastic packaging for MEMS pressure sensor which suggested that the adhesive should be chosen for lower thickness and larger Young’s modulus to make better stability. Li et al [ 6 ] designed a novel piezoresistive pressure sensor with a four-beams-bossed-membrane structure which could improve both sensitivity and linearity. Wang et al [ 7 ] introduced an acoustic pressure sensor with an integrated vacuum cavity that could measure pressure without an external package.…”
Section: Introductionmentioning
confidence: 99%